Transboundary ecological network identification for addressing conservation priorities and landscape ecological risks: Insights from the Altai Mountains - Li An; Lei Shen; Shuai Zhong; Delong Li (Ecological Indicators, 2023)
Insufficient conservation measures and intense human disturbances gave rise to severe landscape ecological risks (LERs) in transboundary areas, highlighting the significance of transboundary ecological networks to maintain ecological functions and landscape integrity. However, previous studies mainly concerned ecological networks in inner regions of a country, and various risk factors remain to be incorporated into ecological network identification to clarify the priorities for transboundary conservation. In this study, we took the Altai Mountains in the transboundary areas of China, Kazakhstan, Russia, and Mongolia as the study area, and identified transboundary ecological networks by integrating LER assessment, ecosystem service evaluation and circuit theory. The results showed that the LER was spatially heterogenous with salient risk exposure in China and Mongolia, and risk disturbance was mainly aggregated in Russia. The identified transboundary ecological networks included ecological sources with an area of 1.6 × 105 km2 and ecological corridors with a total length of 1.1 × 104 km, densely distributed in Russia and Kazakhstan. The area proportion of ecological sources not covered by existing protected areas reached 53.8 %, indicating priorities for further conservation. We put forward management zoning in different LER grades to better support conservation actions on ecological sources. Furthermore, suggestions were proposed to conserve ecological corridors in typical landscapes of the Altai Mountains. The results of this study can facilitate transboundary conservation plannings and policies in the Altai Mountains. Simultaneously, it also provides a reference for effective conservation of risked ecosystems and landscapes in other transboundary areas.